2018
DOI: 10.1177/2167696818781128
|View full text |Cite
|
Sign up to set email alerts
|

Commuter College Student Adjustment: Peer Crowd Affiliation as a Driver of Loneliness, Belongingness, and Risk Behaviors

Abstract: Although previous research has clearly demonstrated the impact that peer crowd affiliation has on socioemotional and risk-related outcomes, very few studies have investigated this relation in samples of emerging adults, and even fewer have focused specifically on commuter college students. Accordingly, the current study aimed to fill this gap in the literature by exploring the relationship between peer crowds and college adjustment at a commuter school. Participants were 663 students at a large public universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Research has found that identification with peer crowds is common among young adults 25 and continues to have significant associations with risk behaviors and indicators of emotional well-being. 26,27 Much work in this area has been done among college students. 5,25,28,29 Kuh and colleagues 30 describe typologies of college students based on factors, such as involvement in academics, sports/recreation, arts/music, and social activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that identification with peer crowds is common among young adults 25 and continues to have significant associations with risk behaviors and indicators of emotional well-being. 26,27 Much work in this area has been done among college students. 5,25,28,29 Kuh and colleagues 30 describe typologies of college students based on factors, such as involvement in academics, sports/recreation, arts/music, and social activities.…”
Section: Introductionmentioning
confidence: 99%
“…Regional studies have found that associations between peer crowd identification and risk behavior among young adults largely mirror those found among adolescents. 3,26,27,31 Lisha and colleagues 3 surveyed young adult bar patrons in California, and found that identifying as hip hop was associated with an increased likelihood of cigarette, e-cigarette, and cigar use, whereas identification with the young professional crowd (akin to the academic crowd in adolescents) was associated with a decreased likelihood of tobacco use. 3 Akin to the academic crowd in adolescents, the young professional crowd prioritizes their careers and is less trend sensitive than the social/partier crowd.…”
Section: Introductionmentioning
confidence: 99%